Tourism Destination Competitiveness and Entrepreneurial Development in South-West Region, Nigeria - Abiola-Oke, Elizabeth (Academica Turistica - Tourism and Innovation Journal, 2024)
The study is based on how tourism destination competitiveness enhances entrepreneurial development. The study aims to assess the factors contributing to the region’s tourism competitiveness and examine the role of entrepreneurial activities in fostering its development. The study adopted a survey research method, a structured questionnaire was used in collecting primary data, and the data were analysed using SMART PLS for structural equation modelling and path analysis. The study’s findings identified the role of tourism competitiveness in entrepreneurship development. The results reveal that facilitating indicators are the most significant measure of destination competitiveness influenced by entrepreneurial development. In contrast, the presence of local businesses at the destination is the most significant measure of entrepreneurial development influenced by destination competitiveness. The observed variables also indicate that destination attraction is critical to the facilitating indicators since it is the most significant variable driving core indicators. Therefore, it is concluded that the competitiveness of tourism destinations plays a significant role in developing entrepreneurship. Keywords: tourism, tourism destination, destination competitiveness, entrepreneurial development